Ironic effects in a simulated penalty shooting task: Is the negative wording in the instruction essential? - Binsch, O.; Oudejans, R. R. D.; Bakker, F. C.; Hoozemans, M. J. M.; Savelsbergh, G. J. P. (International Journal of Sport Psychology, 2010)
Bakker et al. (2006) showed that following a negative instruction not to shoot near the keeper in a penalty shooting task, gaze and shots were ironically more often directed to the keeper. Here we examined whether the negative formulation in the instruction ("not") or mentioning the to-be-avoided area ("keeper") was responsible for ironic effects. Thirty-two male football players performed an indoor penalty-kick task following negatively (not-keeper) and positively (pass-keeper) worded instructions. There was no significant difference between instructions concerning the number of participants who showed ironic effects. Furthermore, regression analyses showed that both instructions affected shooting distance from the keeper to a similar degree and that duration of fixations on the keeper mediated the ironic relationships between both the negative and the positive instructions and performance (ps < .01). It is concluded that in the perceptual-motor domainmentioning what should be avoided and not necessarily the negative wording is responsible for ironic effects and that these effects are mediated by gaze behavior.